Salmonella in food animals and humans in northern Thailand - Padungtod P. (2014)
A study was conducted to describe the epidemiology of Salmonella spp. in chickens, pigs, dairy cows, farm workers with and without livestock contact, and children with diarrhea. Samples were collected in the Chiangmai and Lampoon provinces of northern Thailand during 2000-2003. A total of 2141 samples were processed. The prevalences of Salmonella in chickens at the farm, slaughterhouse and chicken meat at the market were 4%, 9% and 57%, respectively. In pigs, the prevalence at the farm, slaughterhouse and pork at the market were 6%, 28% and 29%, respectively. The prevalence of Salmonella in dairy cows was 3%. Salmonella was isolated from 36% of farm workers with livestock contact and 33% of those with no livestock contact, and from 7% of diarrheal children at the hospital. The longitudinal study of Salmonella in pigs showed that the incidences of Salmonella isolation at the farm, slaughterhouse, and market were 7%, 50% and 20%, respectively. The most frequently isolated serotypes of Salmonella were Weltevreden in chickens and humans, and Rissen in pigs. Serotypes varied between farm, slaughterhouse and market for isolates from chickens and pigs. Antimicrobial resistance was present in isolates from all types of animals and humans in the study, with widespread resistance to tetracycline and nalidixic acid. The proportions of resistant organisms among Salmonella from diarrheal children were high, and higher proportions of multi-drug resistant organisms were observed among Salmonella isolates from farm workers with livestock contact than among isolates from workers with no livestock contact.